The concept of moral integrity and its implications for business - Lisa Schöttl (Hochschule Konstanz Technik, Wirtschaft und Gestaltung (HTWG), Konstanz Institut für Corporate Governance (KICG), 2015)
[Introduction] Regarding moral concerns in the business sphere, integrity is often mentioned as one of the core values that guides the behavior of companies. Daimler for instance states: "Acting with integrity is the central requirement for sustainable success and a maxim that Daimler follows in its worldwide business practices." Reference to integrity is mostly supposed to signal that the company acts morally responsibly. Although some companies specify what acting with integrity means for them, it generally remains unclear what the concept of integrity entails - both broadly speaking and referring to business. This conceptual gap shall be filled by developing a concept of integrity that can be transferred to the business context. For this purpose, the main criteria that constitute moral integrity will be discussed before reflecting on how these could be integrated into a practical and comprehensive concept of corporate integrity.
Keywords: 650; Unternehmensethik; Soziale Werte; Definition